Examination of the social and emotional effects of "Dyslexia" on the learners in private primary schools in Dubai - Sheikh, Salma (2007)
This dissertation was designed to research the social and emotional impact of dyslexia, a specific learning difficulty on learners in private primary schools in Dubai. It is a general fact that dyslexia affects a learner academically, to regard if non- academic skills were also affected which further deteriorated the over all performance of these learners (educationally, socially and emotionally) this research was conducted in three private primary schools in Dubai. Research based recommendations were developed to enhance the future learning processes of these learners. This research was based on qualitative as well as quantitative analysis. Parents, teachers, special educators and the learners themselves were considered for the collection of data findings. Interviews, observations, and questionnaires were used as a source of information for the collection of the data. The findings provided a variety of information that was based on many factors. These factors formed the research recommendations for the learner’s future teachings and include on- time diagnoses and intervention, parent – school partnership, special dyslexia programs, providing social and emotional support, setting realistic goals etc.